Plain language summary of publication to understand the ROSALIA study: a new biosimilar denosumab for bone health - Richard Eastell; Sławomir Jeka; Maryam Lustberg; Colin Edgerton; Paweł Żuchowski; Barbara Vogg (Therapeutic Advances in Musculoskeletal Disease)
Summary What is this summary about? This plain language summary describes the results of a clinical study, ROSALIA , which was published in the Journal of Bone and Mineral Research in 2024. The ROSALIA study looked at whether biosimilar denosumab has the same outcomes as the original-brand reference denosumab for treatment in women with postmenopausal osteoporosis . Why was the ROSALIA study done? The ROSALIA study compared how well biosimilar denosumab works in comparison to reference denosumab in increasing bone density in women with postmenopausal osteoporosis . ROSALIA also looked at how these medicines affect the body and the immune system, their safety, and the results of switching from treatment with reference denosumab to biosimilar denosumab . The study builds on evidence from previous clinical and non-clinical studies comparing the two medicines. Where can I find the original article on which this summary is based? You can read the original article published in the Journal of Bone and Mineral Research at http://dx.doi.org/10.1093/jbmr/zjae016 . The main results and what they mean The ROSALIA study showed that biosimilar denosumab increased bone density, thus reducing the risk of fractures, to the same degree as reference denosumab . Adverse events, which describe reactions to a medicine outside of the expected treatment effects, were similar in incidence for both treatments and mostly mild to moderate. The presence of “anti-drug” antibodies (caused by the immune system trying to neutralize the treatment) was the same in both treatment groups. Both medicines were shown to be processed by the body in the same way. Changing treatment from reference denosumab to biosimilar denosumab did not change how the body reacted to treatment. The results from ROSALIA show that biosimilar denosumab matched reference denosumab and can be used in the same way as reference denosumab for postmenopausal osteoporosis . Furthermore, patients on reference denosumab can be switched to biosimilar denosumab with no issues. Who should read this summary? The summary is intended to provide education about biosimilar denosumab to healthcare professionals, patient advocacy groups, and people who have been prescribed Sandoz denosumab .